Safety and Mechanism of Action of Licensed Vaccine Adjuvants (International Current Pharmaceutical Journal, 2015)
Vaccines are some of the most effective tools for the prevention of infectious diseases. Adjuvants are included in vaccines for a variety of reasons: to increase the breadth of response, to lower antigen dose, to overcome limited immune response in some populations, or to enable complex combination vaccines. This study aims to review the safety of licensed vaccine adjuvants and describe their mechanism of action. Potential publications for inclusion were identified through a direct search of PubMed/Medline database. Results of online literature searches were supplemented by relevant papers cited in published studies along with the authors knowledge of published studies. To date, there are 5 licensed vaccine adjuvants in US and Europe: Aluminum salts (EU, US), MF59 (EU), AS03 (EU), AS04 (EU, US), and virosomes (EU). AS03 is not available as an adjuvant in other vaccines but included within the US governments National Stockpile. All vaccines that contain these adjuvants have been proven safe in clinical trials and post-marketing studies, with the exception of the AS03, for which the rare events of narcolepsy have been reported in some countries. Every adjuvant has a complex and often multifactorial immunological mechanism, usually poorly understood in vivo. The safety profile of an adjuvant, including the actual and hypothetical risks, is a critical component that can speed up or impede adjuvant development. The increasing understanding in adjuvant sciences is fundamental to the further development of new adjuvants.Rambe et al., International Current Pharmaceutical Journal, July 2015, 4(8): 420-431